Use of silver nanoparticles to enhance surface plasmon-coupled emission (SPCE) - Chowdhury, Mustafa H. (2008)
We report that self-assembled monolayers of colloidal silver nanoparticles can increase the intensity of the surface plasmon-coupled emission (SPCE) signal from sulforhodamine 101 (S101). The S101 was spin coated on a glass slide coated with a layer of continuous silver, and a silica layer upon which the nanoparticle layer was self-assembled. Of the various colloid sizes studied, the 40 nm colloids showed both the highest enhancements in the SPCE signal and the largest extent of plasmon coupling, defined as the ratio of SPCE to Free Space signal. Our findings reveal a new technique that can be potentially employed to increase the sensitivity of SPCE applications.